Analisis Ketidaksesuaian Praktik Micro Teaching Dengan Dinamika Pembelajaran Bahasa Indonesia Di Sekolah Dasar Medan - Lot Nola Br Boang Manalu; Erna Tamauli Sihaloho; Lasma Tirtauli Pasaribu; Nurmayani Nurmayani (Jurnal Merah Putih Sekolah Dasar, 2026)
The present investigation is directed at examining how teachers’ fundamental instructional skills are enacted within the learning activities of elementary schools in Medan City. These foundational teaching competencies constitute a critical element of pedagogical expertise, as they underpin the development of learning environments that are effective, engaging, and meaningful for students. A qualitative methodology was adopted, with the study structured as a case study. The participants comprised four elementary school teachers who were deliberately selected through purposive sampling, taking into account their teaching experience. Data collection was conducted by means of semi-structured interviews complemented by document analysis. Subsequently, the gathered data were processed using a descriptive qualitative analytical framework. The findings demonstrate that educators have applied a range of essential teaching skills, encompassing questioning techniques, reinforcement strategies, variation in instructional methods and media, explanatory abilities, lesson initiation, and classroom management. In practice, teachers utilized open-ended questioning to stimulate student engagement, delivered reinforcement in the form of praise and motivational support, and incorporated instructional media—such as digital television, visual images, and educational videos—to facilitate students’ comprehension. Moreover, the study identifies notable distinctions in instructional approaches between teachers in public elementary schools and those in private Islamic elementary institutions, particularly in the application of teaching skills. In general, the effective use of these fundamental teaching competencies fosters more dynamic classroom interaction and enhances students’ motivation to learn. Accordingly, the study underscores the importance of sustained professional development in pedagogical skills as a means to elevate the overall quality of elementary education.   Keywords: Basic Teaching Skills, Pedagogical Competence, Elementary School Learning, Teaching  Strategies, Student Learning Motivation   ABSTRAK   Penelitian ini bertujuan mengkaji penerapan keterampilan dasar mengajar guru dalam proses pembelajaran di sekolah dasar di Kota Medan. Keterampilan tersebut merupakan bagian esensial dari kompetensi pedagogik yang berperan dalam mewujudkan pembelajaran yang efektif, interaktif, dan bermakna. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan empat guru yang dipilih secara purposive berdasarkan pengalaman mengajar. Data diperoleh melalui wawancara semi-terstruktur dan dokumentasi, kemudian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa guru telah mengimplementasikan berbagai keterampilan dasar mengajar, seperti bertanya, memberikan penguatan, menggunakan variasi metode dan media, menjelaskan materi, membuka pembelajaran, serta mengelola kelas. Pertanyaan terbuka digunakan untuk meningkatkan partisipasi siswa, sementara penguatan diberikan melalui pujian dan motivasi. Pemanfaatan media seperti televisi digital, gambar, dan video juga mendukung pemahaman siswa. Selain itu, terdapat perbedaan pendekatan antara guru sekolah negeri dan swasta. Secara umum, penerapan keterampilan tersebut mampu meningkatkan keaktifan dan motivasi belajar siswa, sehingga pengembangan kompetensi pedagogik guru secara berkelanjutan menjadi sangat penting untuk meningkatkan kualitas pembelajaran.